Preconception Immunoglobulins and Complements as Potential Biomarkers in Unexplained Female Infertility in Saudi Arabia - A. Koshak, Emad; S. Aljohani, Hosam; F. Atwah, Ali; A. Aljedani, Rajeh; S. Aljaied, Yasser; A. Gaddoury, Mahmoud (Journal of Fertility Biomarkers, 2023)
Background Immunological abnormalities are currently under scrutiny to potentially unravel the etiology of frustrating cases of unexplained female infertility (UFI). Objectives To explore the prevalence of immunological abnormalities in the levels of total immunoglobulins and complements in the cases of UFI. Methods Females with a history of UFI were included in this cross sectional study. They were consulted at the clinical immunology clinic at the King Abdulaziz University Hospital (KAUH). Their demographics, clinical features, total immunoglobulins and complements tests results were collected and analyzed for any relationship. Results One hundred and twenty-one cases of UFI with an average age of 34 ± 5.6 (range from 23 to 49 years old) were studied. Secondary infertility was predominant in 99 cases (81.8%). An overall prevalence of at least one abnormal level of total immunoglobulins or complements was found in 65 cases (55.1%). The predominant immunological abnormalities were elevated levels of immunoglobulins (hypergammaglobulinemia) in 51 cases (43.2%), high IgG in 26 cases (22%), high IgA in 14 cases (11.9%), and high IgM in 11 cases (9.3%). This was followed by elevated levels of complements (hypercomplementemia) in C4 in nine cases (8.5%). A significant association was found between high C4 group and some parameters of infertility, including primary infertility (p = 0.005), no pregnancy (p = 0.001), no abortion (p = 0.047), in comparison to normal C4 group. Moreover, a statistically significant association was found between high IgA group and abortion in comparison to normal IgA group (p = 0.054). Conclusion At least one abnormal level of total immunoglobulins or complements was detected in more than half of the UFI cases. The commonest abnormalities were hypergammaglobulinemia (IgG, IgM, IgA) and hypercomplementenemia (C4), which showed a potential association with some infertility parameters. These findings may encourage the screening of general immunological tests to explore promising new immunopathology in UFI.
Keywords: Complements; Immunoglobulins; IgA; IgG; IgM; C3; C4; Unexplained Female Infertility